Differences in the characteristics of people who purchase pesticides from shops for self-harm versus those who use pesticides available in the domestic environment in Sri Lanka - Weerasinghe, M; Jobe, L; Konradsen, F; Eddleston, M; Pearson, M; Jayamanne, S; Hawton, K; Gunnell, D; Agampodi, S (Wiley, 2023)
Objective Data from South Asia indicate that for 15%–20% of suicide attempts, pesticides are purchased from shops; otherwise, pesticides are obtained from an individual's house or nearby environment. We aimed to investigate the difference between individuals who directly purchase pesticides from shops for suicide attempts and suicide deaths versus those related to accessing the pesticides from an individual's house or nearby environment. Methods We conducted two comparative studies in rural Sri Lanka: (1) non-fatal shop cases (n = 50) were survivors of self-poisoning with pesticides who ingested the pesticides after purchasing them from a shop; non-fatal domestic cases (n = 192) were survivors who accessed pesticides from their house or nearby environment. (2) fatal shop cases (n = 50) were individuals who died after ingesting pesticides they purchased for the act; fatal domestic cases (n = 102) were patients who died after ingesting pesticides they accessed at house or nearby environment. Logistic regression analysis was used to assess the characteristics which distinguished between the shop and domestic cases. Results Data indicate that 20.7% and 32.9% of individuals who used pesticides for suicide attempts and suicide deaths had purchased them from shops, respectively. Being a non-farmer was the main distinguishing characteristic of shop cases: adjusted odds ratios (AOR) 8.9, 95% confidence intervals (CI) 3.2–24.4 for non-fatal shop cases, and AOR 4.0, 95% CI 1.5–10.6 for fatal shop cases. Non-fatal shop cases also had higher suicide intent (AOR 3.0, CI 1.0–8.9), and ingesting an insecticide (AOR 4.8, CI 1.8–1.0–8.9) than non-fatal domestic cases. Conclusion A high suicide intent of individuals who purchase pesticides for the event explains the high proportion of such fatal cases. Such high suicide intent makes the prevention implications difficult to spell out for those individuals who purchase pesticides for self-poisoning. However, our findings are valuable for clinicians to assess pesticide poisoning cases in hospitals.